PENERAPAN MODEL PEMBELAJARAN KOOPERATIF DENGAN PENDEKATAN PAIR CHECKS UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN HIDROKARBON DI SMAN 3 DURI - PUTRI ADE RAHMA YULIS (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
Based on the information obtained student learning outcomes are still relatively low. The reason for this is still applied learning model that is dominated by teachers, so that students are not actively involved in the learning process. To overcome this, efforts have been made to change with group learning. The result of group learning was not maximal because of the dominance in the group, so the students' understanding is uneven. As a result student learning outcomes are still many below assigned the minimum criteria. Based on this, the authors conducted a cooperative learning model study with pair checks approach. Application of this learning model is expected to improve student achievement as a whole. That is because in this learning model students are trained sharing skills by working in pairs and pairwise checking arrangements, so no more terms dominate in the group. This form of research is an experiment with pretest and posttest design. The research sample consisted of two classes of X SMAN 3 Duri, class X.7 as experiment class and class X.10 as control class. Processed data are pretest and posttest values on hydrocarbon subject. Hypothesis test data processing using t-test formula obtained t-quantification bigger than t-table that is 2,65> 1,67, meaning hypochetical application of cooperative learning model with pair checks approach can improve student achievement on hydrocarbon subject in SMAN 3 Duri accepted. Keywords: Cooperative Learning, Pair Checks Approach, Learning Achievement